ANALISIS PENGARUH DAYA SAING DAERAH DAN TINGKAT PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI KABUPATEN DAN KOTA DI JAWA TENGAH - Aji Priambodo (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This research is to analyze the influence of Regional Competitiveness andUnemployment Rate on the Economic Growth Rate of Regencies and Cities in CentralJava 2018-2021. The data used is secondary data in the form of panel data in 35regencies and cities in Central Java Province. The results of panel data analysis showthat regional competitiveness and the unemployment rate simultaneously affect therate of economic growth in regencies/cities in Central Java 2018-2019, while partiallyregional competitiveness has a positive and significant influence on the rate ofeconomic growth in regencies and cities in Central Java in 2018-2021 and theunemployment rate has a negative and significant influence on the rate of economicgrowth in Regencies and Cities in Central Java in 2018-2021.